Brahmi inscriptions of the Gupta period - Temples of India Project Team (Jio Institute, 2024)
The Charchoma Shiva Temple has two Brahmi inscriptions of Gupta letters. One of the inscriptions is placed on the entrance, outside the main temple structure. The language used in this inscription is Sanskrit.